PROSPECT BUDIDAYA USAHA LEBAH MADU (Trigona sp) DENGAN METODE TOPING DAN STUP - Safrin Edy; Laode Al Hemawan Ardi (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2020)
This study aims to analyze the feasibility of the business and analyze the opportunities and threats of Trigona Ongka farm in Laompo Village, Batauga District, South Buton Regency. The research was conducted from January to February 2020 in Laompo Village, Batauga District, South Buton Regency. The sample in this study was 1 (one) honeybee breeders (Trigona sp). The method used is the independent sample t-test and the R / C feasibility analysis. Business opportunities and threats are analyzed qualitatively. The results showed that the business feasibility of Trigona sp honey bee livestock through the STUP and topping method was 1.5, (R/C > 1), meaning that each additional cost incurred resulted in a larger increase in revenue as much as IDR 1,400,000 for the STUP method and IDR 1,500,000 for the topping method instead of additional costs or simply profitable business activities. The honey bee livestock business opportunity of Trigona sp, namely honey as a favorite that is popular, relatively stable price, partially known production of the community, the location is easy to reach by vehicles, the availability of large land for business development. While the threat of Trigona sp honey bee livestock, namely: lack of environmental carrying capacity, so that environmental improvements and increasing the number of bee colonies are needed to increase honey production, do not have a product brand to be widely commercialized, product quality standardization is still poorly understood by breeders, there is no internal coordination between breeders to strengthen institutions and lack of access to assistance from capital institutions in terms of capital. Keywords: Prospects, Business Feasibility, Honey Bees